2010
DOI: 10.1073/pnas.1001098107
|View full text |Cite
|
Sign up to set email alerts
|

Apparent failure of the Born–Oppenheimer static surface model for vibrational excitation of molecular hydrogen on copper

Abstract: The accuracy of dynamical models for reactive scattering of molecular hydrogen, H 2 , from metal surfaces is relevant to the validation of first principles electronic structure methods for molecules interacting with metal surfaces. The ability to validate such methods is important to progress in modeling heterogeneous catalysis. Here, we study vibrational excitation of H 2 on Cu(111) using the Born-Oppenheimer static surface model. The potential energy surface (PES) used was validated previously by calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(119 citation statements)
references
References 47 publications
5
113
1
Order By: Relevance
“…On the other hand, Sitz and co. 46 have found that a significant amount of energy in H 2 is lost to the surface upon scattering from Cu(100). Recently, 47 it has been hypothesized, based on an exhaustive analysis of experimental data, that phonons may play a significant role in promoting vibrational excitation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Sitz and co. 46 have found that a significant amount of energy in H 2 is lost to the surface upon scattering from Cu(100). Recently, 47 it has been hypothesized, based on an exhaustive analysis of experimental data, that phonons may play a significant role in promoting vibrational excitation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of scattering of (v = 0, J = 0) H 2 , our results predict that the vibrationally excited molecules have transfered less than 3 meV to the surface, in the range of E inc considered (0.6-1.2 eV). This amount of energy is far below what can be reasonably expected for this kind of experiment, which is around 30% of the incidence energy [34]. This analysis indicates that other surface degrees of freedom with a more efficient energy transfer should be considered to achieve a better description of the vibrationally inelastic scattering experiments [51] than obtained so far [34].…”
Section: Thermal Averagesmentioning
confidence: 63%
“…In [34] it is suggested that this discrepancy could be reduced by taking into account the thermal motion of the surface. In fact, the intensity of the TOF signal reflects not only the probability of scattering to the (v = 1, J = 3) state, but also the energy loss to the surface (including loss to surface phonons), since molecules which have lost part of their incidence energy travel more slowly in the detection zone and thereby increase the detection signal [34,51]. Díaz et al showed that the most important contribution to the (v = 1, J = 3) TOF signal comes from the (v = 0, J = 5) initial state [16].…”
Section: Thermal Averagesmentioning
confidence: 99%
See 2 more Smart Citations